Molecular Docking Studies of Phytocompounds in Common Weeds with AChE Proteins of Aphids and Beetles. Issue 1 (2nd January 2020) - Sinha, Somya; Pant, Kumud; Pal, Manoj; Sharma, Promila; Anand, Jigisha; Pant, Bhasker; Verma, Devvret; Kumar, Rohit; Tripathi, Yamini; Birla, Kartikey; Agarwal, Priya
Abstract: Aphids and beetles are known to be the most destructive house hold pests. The insecticides used against these pests are known to be toxic and harmful for plants, animals and human beings. Weeds are the unwanted plants that usually grow undesirably in a particular condition and hinder the growth of most of the crops. These undesired plants were reported to have several medicinal as well as insecticidal properties. Parthenium hysterophorus, Lantana camara and Alternanthera sessilis are the most common invasive species containing various phytocompounds that shows insecticidal properties. The literature finding suggests that targeting AChE protein of these pests would result in the excitation of their muscles and finally results in the death of these pests. In the present study homology modeling of the AChE of the studied pests was generated using SWISS-MODEL. Phytocompounds of P. hysterophorus, L. camara and A. sessilis was used as a ligand molecule. Molecular docking and ADMET analysis was also performed. Docking results showed that kaempferol exhibited least binding energy with the proteins of R. padi, A. pisum, M. persicae i.e. -102.38 kcal.mol, -98.64 kcal/mol, -92.4516 kcal/mol respectively. Phytocompounds of L. camara showed least binding energy when docked with AChE ( L. decemlineata ) and AChE ( O. taurus ) i.e. -98.6 and -87.4555 kcal/mol respectively. Docking and ADMET study suggest that Kaempferol, Stigmasterol and Lantadene can act as potential bio or green insecticides or pesticide, , although the toxicity level of the compounds may differ as per application.